Changing Some Parameters of The Fetus Head - Akhmedova S. M; Mansurova D.A; Niyozov N.K; Nisanbaeva A.U (Zien Journals, 2023)
The characteristic of the growth rates of various indicators at the stages of screening examination allows us to judge the adaptation processes occurring in the process of fetal growth. And in fetuses of pregnant women in a state of hypothyroidism, the intensity of growth of head parameters was less compared with the parameters of fetuses of healthy pregnant women. In fetuses of pregnant women in a state of hypothyroidism, the biparietal head size is significantly smaller at the stage of the second screening examination than in fetuses of healthy pregnant women
Keywords: hypothyroidism; experimental hypothyroidism; thyroid pathology